Korea economic, political and social issues (Nova Science, 2008)
"Korea is known as the "land of the morning calm", an expression that comes from the ancient Korean dynasty of Koryo (918-1392). Koryo means "high" and "clear", thus symbolising the clear blue skies of Korea. Thus the beautiful nature of Korea is expressed through its ancient name. The Korean Peninsula adjoins China in the north-west, while Japan lies to the south-east. Throughout history, this geopolitical location has led to much hardship for Korea, including Japan's colonial rule (1910-1945), the tragic division into South and North Korea at the end of Word War II, and the devastating Korean War (1950-1953). Nevertheless, thanks to the successful implementation of a growth-oriented economic policy from the 1960s, Korea has enjoyed remarkable economic development, which has become known as the "Miracle on the Han-gang River".With the international exposure of the 24th Summer Olympics which were hosted in Seoul in 1988, Korea's economic achievements and the richness of its unique culture were revealed to the world. More recently, Korea's continued economic advancement was evidenced by its membership in the OECD and WTO in 1996. And, while Korea was hit hard by the Asian financial crisis in late 1997, it is now well on the road to recovery as a result of the new administration's effective leadership and the indefatigable spirit of the Korean people. Korea is striving to emerge as an exemplary member of the global community by actively opening its markets and welcoming foreign investment into the country. Moreover, considerable efforts are being exerted to attract wider attention to its traditional culture and arts, which uniquely reflect Korea's history of several thousand years. This book focuses on economic, political and social issues."-- Preface.